HASRAT KONSUMEN YANG MENGIKAT (BINDING CUSTOMER DESIRES) - Sulis Riptiono (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2017)
Desires in the marketing context are defined as the phase of the sequence in marketing that begins with the creation of awareness, and then interest is usually at the stage when the customer really wants the product or service that is being marketed. Desire is a form that is seen as a precursor in making actual purchases. Desire is more than want of consumers to try and have the product, the consumer's curiosity towards the product is directed to the interest to buy. Desires are created to convince consumers that they have a great desire to have the product or service offered according to their needs. Desire is not enough to explain its impact on increasing consumer buying interest and consumer behavior, but the desire that has binding properties to consumers that called binding costumer desires can increase buying and behavioral interests. Binding costumer desires is used to fill the research gap about subjective norms against purchase intention by using the basic theory of the theory of reaction action (TRA) and theory of planned behavior (TPB).